2020
DOI: 10.1101/2020.12.22.20248713
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of mHealth interventions on antenatal and postnatal care utilization in low and middle-income countries: A Systematic Review and Meta-Analysis

Abstract: ObjectiveTo evaluate the effectiveness of mHealth interventions on antenatal and postnatal care utilization in low and middle-income countries.DesignSystematic review and meta-analysisSettingStudies from low and middle-income countries were included for analysis.ParticipantsWe searched the literature through major electronic databases such as PubMed, MEDLINE, Embase, Cochrane, Scopus, CINAHL, Clinical key, Google Scholar, Ovid databases with selected keywords, and explored the reference list of articles. Meta-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…In the present study, we found that antenatal mothers who used mobile health interventions had an approximately two times higher chance of receiving ANC check-ups than women who did not use any mobile health applications or did not receive any short message services, which is higher than in another systematic review conducted in a population of LMICs in the time frame from 2008-2020 (OR = 1.89, 95% CI: 1.49-2.19) [30]. Despite the fact that most people exhibit techno-skepticism (i.e., a skeptical attitude toward technology), this meta-analysis revealed that mHealth has the potential to increase antenatal attendance when compared to conventional approaches.…”
Section: Discussioncontrasting
confidence: 66%
“…In the present study, we found that antenatal mothers who used mobile health interventions had an approximately two times higher chance of receiving ANC check-ups than women who did not use any mobile health applications or did not receive any short message services, which is higher than in another systematic review conducted in a population of LMICs in the time frame from 2008-2020 (OR = 1.89, 95% CI: 1.49-2.19) [30]. Despite the fact that most people exhibit techno-skepticism (i.e., a skeptical attitude toward technology), this meta-analysis revealed that mHealth has the potential to increase antenatal attendance when compared to conventional approaches.…”
Section: Discussioncontrasting
confidence: 66%
“…mHealth interventions are implemented and researched extensively. Evidence from systematic reviews shows that mHealth interventions are effective in increasing the use of antenatal and postnatal care, including attendance at antenatal and postnatal care check-ups, facility-based deliveries, and skilled attendance at birth and vaccination rates [ 22 ]. Conversely, another systematic review and meta-analysis concluded that most studies conducted in low- and middle-income countries are of poor methodological quality, and few have evaluated impacts on patient outcomes [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on testing mHealth interventions for postnatal care in India is limited [ 34 , 35 ]. And our study results indicate that new mothers who used the service found that the intervention to be informative, timely and empowering.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in India, studies on testing mHealth interventions for postnatal care are limited [ 34 , 35 ]. To address the above issues, an innovative solution to provide ongoing follow-up service to new mothers at discharge was designed.…”
Section: Introductionmentioning
confidence: 99%